A Historical Perspective of Mangalavattiyam - Suhanya, A. (International Research Journal of Tamil, 2021)
From the earliest days of the Tamil music tradition, music was considered to be a combination of vocal music, instrumental music and dance. Each of these musical genres is closely intertwined. Knowledge of one helps to know about the other. Instrumental music has been interpreted as accompaniment to solo music and dance and as a solo specialty. In Bharata's book 'Natyashasthram', musical instruments are generally divided into four categories as nerve (tata), hole (kasira), skin (avanatta), kana (kanja). In this context, it is a research paper on the history and use of the Nagaswaram and thavil instruments, which are referred to today as the Mangala Vaathyam, which the Tamils have merged with their culture. This article also examines in detail the ideological changes that have taken place over time in the use of these two musical instruments. At the same time, the use of these instruments in the sociological context is taken into account. Finally, this article is a historical study of the lineage of musicians who have mastered these instruments.
Keywords: Mangala Vathyam; Naagaswaram; Cultural Identity; Music; Cultural Individuality